The Social Construction of Shariah-Compliant Hotels: Exploring the Interplay of Conservatism and Politics in Public Policy - Adnan, Muhammad (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
This research emphasizes the promotion of halal tourism, with a specific focus on the hotel industry as a key indicator. The objective of this study is to elucidate the social construction related to Sharia-based hotels, delving into the intricate relationship between religious values, political ideology, and considerations of public policy. Additionally, the research aims to examine the compliance conditions associated with Sharia labeling within these hotels. Employing qualitative methods, the study employs content analysis within the framework of existing policies and social construction. Furthermore, it utilizes participatory approaches involving five Sharia property business actors to assess the extent of Sharia practices within the hotel industry in Semarang City. The findings reveal that the management and services offered by Islamic hotel businesses do not comprehensively reflect Islamic understanding and identity. It is noteworthy that many practitioners in the Islamic hotel industry tend to base their Sharia concepts on consultations with Islamic religious leaders. Additionally, the incorporation of Sharia rules across various sectors, particularly within the tourism industry, is identified as potentially fostering a standardization of values. In response, the study suggests that policies and regulations should prioritize principles of public justice and guarantee equal constitutional rights to mitigate such homogeneity and preserve cultural diversity.